Lénine philosophe : examen critique des fondements philosophiques du léninisme - Pannekoek, Anton; Mattick, Paul; Korsch, Karl (Paris : René Lefeuvre, 1970)
Fonds Perrone
Frans
Monografie
Keywords: leninisme